Impact of shipping alliances on the competitiveness of the top busiest ports: Port of Singapore, Port Klang and Port of Tanjung Pelepas - Xie, Amanda Jiamin (2016)
The Southeast Asia region is one of the busiest port regions in the world, where Port of Singapore, Port Klang and Port of Tanjung Pelepas is located. This competitiveness of these hub ports were evaluated using Porter’s Diamond Model, and it was seen that the Port of Singapore was the most competitive. In the past 10 years, there have been increasing consolidation in the market through the formation of shipping alliances. The rise of shipping alliances have affected the competitiveness of ports around the world due to their scale of operations. Unlike shipping lines, the decision process of alliances for port selected is multi-faceted and involves all members of the alliances. Thus, this paper thus seeks to explore and analyse the impact of shipping alliances on the competiveness of ports. Through a questionnaire conducted among members of alliances, it revealed that ‘Geographical Location’, ‘Port Connectivity’, ‘Port Reliability’, ‘Preferences of Shipping Line’s Clients/Shippers’, ‘Adequacy of Depth Alongside’, ‘Adequacy of Container Handling Equipment’, ‘Terminal Handling Charges’, ‘Adequacy of Quay Length’ were deemed as more important factors. Questionnaire results and statistical analysis of the port calls of the alliances showed that Singapore remained as the most competitive port. The findings from this study provide insights on what alliances look out for when selecting a port of call and how ports can maintain competitiveness.